Activity To Prevent Risk Factors For Pregnant Mothers As Early As Possible in the Working Area of Pasar Ikan Health Center, Malabero Village, Bengkulu City - Ice Rakizah Syafrie; Diyah Tepi Rahmawati (Jurnal PADAMU NEGERI (Pengabdian pada Masyarakat Bidang Eksakta), 2022)
In 2020 in Bengkulu Province there were still 32 maternal deaths. Malabero is one of the villages in Teluk Segara District, Bengkulu City, which is located in the city center, is a fishing village area and includes the working area of the Pasar Ikan Health Center. There were 352 visits by pregnant women during 2020 at the Puskesmas (Bengkulu Health Office, 2021). The high number of pregnant women and the number of deaths due to complications require that health workers, especially midwives, are able to detect risk factors in pregnant women. High-risk pregnancies are pregnant women with various risk factors that can cause complications such as pain or bleeding, disability, discomfort during pregnancy and after delivery, can threaten the life of the mother and fetus. The community service team from FIKes Unived held active activities to prevent risk factors for pregnant women aimed at early detection of high-risk pregnancies. The method used in this service is by providing education using maternal and child health books (KIA). By holding this health education, it is hoped that pregnant women will be able to increase knowledge and prevention. Risk factors for pregnant women include age, parity, height, blood pressure, upper arm circumference, birth spacing, hemoglobin levels, body weight, history of pregnancy-delivery-partum, fetal position abnormalities, large fetal abnormalities.